Perception of dentists regarding brain drain in Punjab, Pakistan: A cross-sectional survey - Arooj Ul Hassan; Naiha Muzamil; Mehrin Wajahat; Zunaira Iqbal; Obaid Bajwa (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: Brain drain is a term coined for the migration of highly skilled professionals from the country of their origin to more developed countries. As the trend of moving abroad is on a rise, ever since, it is causing a shortage of dental professionals in our country. The objective of our study is to determine the factors that would compel the dentists of Punjab, Pakistan, to move abroad and how to prevent this migration. METHODOLOGY: It was a cross-sectional survey. Data was collected through a self-constructed and validated questionnaire. The study was done in dental colleges in Punjab, and the duration of the study was one year. The questionnaire was distributed both by hand and via digital sources. RESULTS: There were 155 (33.4%) participants, who were planning to go abroad for higher education, and 274 (59%) had not planned to go out of the country for further studies. Among the study participants, 50 (32.3%) participants were planning to move to the United Kingdom, whereas 23 (14.8%) participants were planning to go to Australia, 44 (28.3%) wanted to move to the US, 10 (6.4%) to Canada and the rest (18%) had plans to move to any other country. CONCLUSION: The majority of dental graduates wish to go abroad for their post-graduation. The dentists of Punjab were willing to serve their country, provided the economic and political situations improved.